Airway pressure release ventilation mode in lung injury - Al-Ahmad, Abdullmohsen Mohammed (2017)
Airway pressure release ventilation (APRV) is a promising, unconventional mode of ventilation for the treatment of various respiratory diseases, including acute respiratory distress syndrome (ARDS). However, despite increasing global use and reported advantages of APRV over other modes, definitive conclusions cannot be drawn due to several concerns. First, the major confusion between APRV and other, similar modes, such as bi-phasic positive airway pressure (BIPAP). Second, clinical and methodological heterogeneity among published studies of APRV are understandably extensive, which contributes to outcome variability. Third, the absence of consensus on a standard protocol with clear rationale for the settings. This thesis provides an overview of the spectrum of ventilator settings that may be designated as APRV, summarises the research and clinical use status of APRV, exemplifies the need to clarify the characteristics that comprise the mode, and to assure reports of APRV use, from case reports through RCTs, including adequate data for a proper assessment. It encourages continued publication of observational as well as experimental clinical trial data, and discusses the feasibility of analysis strategies that may expand the information available from small patient samples. It also presents an unpublished, comprehensive, multifaceted clinical practice protocol (Al-ahmad protocol) for the use of APRV.